Occupational safety practices and individual and organizational outcome: a systematic literature review - Zgair, Laith Ali; Zafir Khan Mohamed Makhbul; Nur Atiqah Abdullah; Ahmad Raflis Che Omar (Penerbit Universiti Kebangsaan Malaysia, 2023)
Occupational safety varies across countries and industries. This study therefore conducts a Systematic Literature Review to suggest the direction for future work and to identify the effect of safety on individual and organizational outcomes. Articles between 2010-2021 were extracted and screened and a total of 70 articles was reviewed. The findings indicated that safety is essential for individual and organizational outcomes. Safety practices can improve on employee performance, satisfaction, commitment and engagement. They also exert critical impact on organizational outcome such as organizational justice, HRM practice, organizational culture, and organizational identification. In the context of safety compliance and safety practice, and safety performance, the important variables are leadership style and total quality management (TQM). Together with occupational safety, these variables can predict individual and organisational outcomes. Safety at workplace should be a concern for all stakeholders, and this can be observed through implementing effective leadership and establishing safety culture.